Vascular endothelial growth factor receptors VEGFR-2 and VEGFR-3 are localized primarily to the vasculature in human primary solid cancers. - Smith, N; Baker, D; James, N; Ratcliffe, K; Jenkins, M; Ashton, SE; Sproat, G; Swann, R; Gray, N; Ryan, A; Jürgensmeier, J; Womack, C (2010)
PURPOSE: Vascular endothelial growth factor (VEGF) signaling is key to tumor angiogenesis and is an important target in the development of anticancer drugs. However, VEGF receptor (VEGFR) expression in human cancers, particularly the relative expression of VEGFR-2 and VEGFR-3 in tumor vasculature versus tumor cells, is poorly defined. EXPERIMENTAL DESIGN: VEGFR-2- and VEGFR-3-specific antibodies were identified and used in the immunohistochemical analysis of human primary cancers and normal tissue. The relative vascular localization of both receptors in colorectal and breast cancers was determined by coimmunofluorescence with vascular markers. RESULTS: VEGFR-2 and VEGFR-3 were expressed on vascular endothelium but not on malignant cells in 13 common human solid tumor types (n > 400, bladder, breast, colorectal, head and neck, liver, lung, skin, ovarian, pancreatic, prostate, renal, stomach, and thyroid). The signal intensity of both receptors was significantly greater in vessels associated with malignant colorectal, lung, and breast than adjacent nontumor tissue. In colorectal cancers, VEGFR-2 was expressed on both intratumoral blood and lymphatic vessels, whereas VEGFR-3 was found predominantly on lymphatic vessels. In breast cancers, both receptors were localized to and upregulated on blood vessels. CONCLUSIONS: VEGFR-2 and VEGFR-3 are primarily localized to, and significantly upregulated on, tumor vasculature (blood and/or lymphatic) supporting the majority of solid cancers. The primary clinical mechanism of action of VEGF signaling inhibitors is likely to be through the targeting of tumor vessels rather than tumor cells. The upregulation of VEGFR-3 on tumor blood vessels indicates a potential additional antiangiogenic effect for dual VEGFR-2/VEGFR-3-targeted therapy.